Impact of organizational culture on employees’ performance: A study in multinational corporations in Sarawak - Lau, Chien Jie Ivy (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at https://ijbt.unimap.edu.my